KARAKTERISASI PISANG REJANG TETRAPLOID HASIL INDUKSI DENGAN ORYZALIN [Characterization of tetraploid Pisang Rejang induced by oryzalin] - Poerba, Yuyu Suryasari; Handayani, T; Witjaksono, Witjaksono (BERITA BIOLOGI, 2017)
Triploid banana cultivar is the most desirable cultivar in banana industry because of its higher yield compared to its diploid cultivar. Â The Â triploid cultivar can be produced by crossing tetraploid with diploid cultivar. Â However, tetraploid banana cultivar is rarely existed naturally. Â Induced tetraploid of Pisang Rejang was produced using oryzalin. The present research was conducted to characterize tetraploid Pisang Rejang (Musa acuminata, AAAA genome) induced by in-vitro oryzalin treatment from diploid Pisang Rejang. Ploidy level, molecular and morphotaxonomic characters were observed. Â Ploidy identification of induced Pisang Rejang was conducted using Flowcytometer. Â Molecular characterization was done using RAPD and ISSR markers. Morphology characters were observed based on UPOV (2010). The results showed that tetraploid plants have similar genetic properties with their diploid controls as shown by genetic identity of 0.9901 â 0.9935. The tetraploids were differed from their diploid plants in plan habit and diameter of fruit. Â The tetraploid plants produce fewer suckers, drooping leaves and broader fruits compared to its diploid control.